ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PEMBANGUNAN DI PROVINSI KALIMANTAN - NADYA CINTHYA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research is conducted to (1) find out whether the content of natural resources, demographic condition, mobility of goods and services, concentration of economic activity and development fund allocation together significantly influence the development inequality in South Kalimantan Province; (2) to know the most dominant factor influencing development disparity in South Kalimantan Province. Technique of data analysis in this research is Williamson index analysis and panel data regression analysis with Fixed Effect model.The result of panel data regression states that natural resource content, demographic condition, mobility of goods and services, concentration of economic activity and development fund allocation together have significant effect on development disparity in South Kalimantan Province. Demographic condition factor is the most dominant factor affecting development disparity in South Kalimantan Province in 2012-2016.  Keywords: Development Disparity, Natural Resource Content, Demographic Condition, Mobility of Goods and Services, Concentration of Economic Activity, Development Fund Allocation.